2021
DOI: 10.3390/brainsci11020212
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Safety and Tolerability of Transcranial Direct Current Stimulation in Children and Adolescents

Abstract: Background: Transcranial direct current stimulation (tDCS) is a safe, tolerable, and acceptable technique in adults. However, there is limited evidence for its safety in youth. Although limited, there are a handful of important empirical articles that have evaluated safety and tolerability outcomes in youth. However, a synthesis of pediatric safety studies is not currently available. Objective: To synthesize objective evidence regarding the safety and tolerability of pediatric tDCS based on the current state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…All participants underwent daily sessions of 1.0 mA 20 min tDCS on 20 consecutive weekdays [ 50 , 68 ]. We used a HDC stimulator (Newronika TM , Milan, Italy) connected to two 5 cm × 5 cm conductive-rubber electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants underwent daily sessions of 1.0 mA 20 min tDCS on 20 consecutive weekdays [ 50 , 68 ]. We used a HDC stimulator (Newronika TM , Milan, Italy) connected to two 5 cm × 5 cm conductive-rubber electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…tDCS can be used alone or in combination with other interventions, such as psychotherapy [ 47 ] or cognitive training [ 48 ]. In recent years, tDCS has also been used to treat children and adults with ASD, with no serious adverse events and encouraging results in terms of feasibility, efficacy, and tolerability [ 49 , 50 ]. Of particular interest, preliminary studies have shown tDCS to improve the core symptoms of ASD in addition to reducing behavioral symptoms [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it analyzes the differences between the situation at the final stage of the study and at the beginning of the study ( = Stage 4 -Stage 1). Table 5 shows significant positive relationships between the changes in two questions in ZUNG (10,16) and negative associations with two questions of EDE-Q (4, 23). Compared with sham tDCS, active tDCS significantly improved self-evaluation based on one's body shape (EDE-Q 23) and significantly decreased the need of excessive control over calorie intake (EDE-Q 4) in a follow-up after 4 weeks (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a modern, well-tolerated method, which can be easily applied by trained personnel. It is assumed to be a safe technique (8)(9)(10), and the adverse effects are overall mild. The advantages of this method are low purchase costs and great therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…As for potential risks of tDCS, guidelines report no serious adverse events in over 18,000 sessions of low-intensity transcranial electrical stimulation in pediatric and adult patients, as well as in healthy subjects ( 89 ). Current data also specifically emphasize the feasibility, tolerability, and safety of tDCS in children and adolescents ( 45 , 63 , 90 ). Adverse effects of tDCS in children and adolescents were described as mild and transient, including tingling (11.5%), itching (5.8%), redness (4.7%), and scalp discomfort (3.1%) ( 91 ).…”
Section: Methods and Analysismentioning
confidence: 99%